Cigarette smoking/cessation and metabolic syndrome. (1st December 2016) - Kolovou, Genovefa D.; Kolovou, Vana; Mavrogeni, Sophie
Abstract: The metabolic syndrome (MetS) is a common cluster of pre-morbid, modified metabolic–vascular risk factors/diseases (visceral obesity, hyperglycaemia, dyslipidaemia and hypertension) associated with increased cardiovascular (CV) morbidity, fatty liver and risk of cancer. Several studies reported a higher incidence of MetS in smokers. Cigarette smoking plays a substantial role in the pathogenesis of numerous chronic diseases such as CV disease (CVD), cancer, lung disease and others. However, due to the existence of the so-called "smoking paradox", the impact of this risk factor on CVD mortality is still not clear. Smoking cigarettes may increase risk of MetS or worsen it by numerous mechanisms. Furthermore, individuals who quit smoking tend to increase their body weight. The possibility of gaining weight can stop smokers from quitting and increases the risk of relapse, particularly in women. Herein, we review the cigarette smoking status (active/cessation) in relation to the MetS.